Causal Modelling of Factors Influencing Quality of Nursing Care in China - Xue, Xiaolu; Kunaviktikul, Wipada; Abhicharttibutra, Kulwadee; Wichaikhum, Orn-Anong (Pacific Rim International Journal of Nursing Research, 2023)
The quality of nursing care is essential and contributes to restoring people’s health and well-being, especially when people are hospitalized. Various factors relating to the quality of nursing care have been identified, including nursing shortages. However, in China, there has been little research undertaken on factors influencing nursing care quality. This cross-sectional study aimed to develop and test the Chinese Model of Quality Nursing Care. A multi-stage, proportional stratified random sampling was used to recruit 784 registered nurses in three affiliated hospitals of a medical university in the People’s Republic of China. Eight Instruments were used for data collection: a demographic data form, the Good Nursing Care Scale, the Nurse Staffing Item, the Practice Environment Scale of the Nursing Work Index, the 3-item Utrecht Work Engagement Scale, the Psychological Empowerment Scale, the High-performance Work Systems Scale, the 8-item Survey of Perceived Organizational Support. In addition, the Analysis of Moment Structure software program was used to test the hypothesized model. Results indicated that the modified model fitted the empirical data and explained 31% of the variance in the quality of nursing care. Nursing practice environment, psychological empowerment and work engagement had positive direct effects on the quality of nursing care, with the nursing practice environment having the strongest total effect. Nursing practice environment, high-performance work systems, and perceived organizational support indirectly positively affected the quality of nursing care through psychological empowerment and work engagement. Unexpectedly, the patient-to-nurse ratio had no significant influence on the quality of nursing care. The results support the need for hospital managers to take action to improve the organizational support and work environment and create high-performance work systems to retain more nurses and midwives to enhance the quality of nursing care. The model requires further testing in practice and possible refinement.